Pengaruh Metode Pembelajaran Outdoor Learning Terhadap Kemampuan Berpikir Kreatif dan Kemampuan Menulis Puisi Siswa Kelas V SDN 59 Kota Bengkulu - Randa, Arolan Agusti (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to describe the Effect of Outdoor Learning Methods on Creative Thinking Ability and Poetry Writing Ability in Class V Sdn 59 Bengkulu City. This research is a quantitative study with the research method used is a quasi experimental method and the design used is The Matching Only Pretest-Posttest Control Group Design. The population of this research is 60 students of V State Elementary School 59 in Bengkulu City. The total number of students is in two classes. The research sample was taken using a total random sampling technique, in this study using two classes to obtain a VA class of 30 students as a control class, a VB class of 30 students as an experimental class, and a VA class in SD Negeri 20 Bengkulu City as an instrument trial class . The research instrument was in the form of a test sheet. Based on the hypothesis test using the ONE WAY ANOVA test with the help of SPSS 16.0, it was found that: 1) There is an influence of the outdoor learning method on the ability to write poetry for fifth grade students of SD Negeri 59 Bengkulu City. 2) There is an influence of the ability to think creatively on the ability to write poetry for fifth grade students at SD Negeri 59 Bengkulu City.